“THIS IS A GREAT MYSTERY ....” (EPH 5:32): The Concept of Family in the Bible - Pamplany, Joseph (Asian Horizons, 2014)
Marriage and the family were God’s idea and divine covenant between one man and one woman, a lifelong union of two partners created in God’s image to govern and manage the earth for him. Gen 1:26-27 and 5:1-3 emphasise that humankind is created as a community not as an individual; consequently it is not the individual but the community (family) who fully reflects the image and likeness of God. However the bible does not conceive any contradiction between individual and family. God designed it so that the man needs the woman and the woman needs the man (1 Cor 11:11). Both are equal persons and yet have distinct roles to fulfil. If sex is removed from the context of the marriage commitment, sex becomes a superfluous object of hedonism. Bible is of the opinion that God created marriage for a purpose bigger than itself: Marriage is a picture of the believer’s relationship with God. Marriage is an earthly picture of the spiritual relationship that exists between Christ, the bridegroom, and the church, His bride. In this respect family life is a great mystery (Eph 5:23). Family must be the subject and object of evangelisation, liberation and humanisation.